Temporary Employment in Tourism Activities: Regional differences in Spain - Diana Perez-Dacal; Yolanda Pena-Boquete (European Regional Science Association (ERSA), 2011)
The great capacity of tourism to provide employment, especially between groups of workers with a more difficult insertion in the labour market, is one of its most well-known positive aspects. However Tourism employment is often described as low skilled, which is associated with average lower wages, higher percentage of fixed-term contracts, and longer working day than other industries. Nevertheless, this is not true for all tourism activities. Although this description could be close for hotels and restaurants labour market, it is completely different for land transport, travel agencies and tour operators activities. This could be related with the fact that each characteristic tourism industry provides a different percentage of his output to tourists, as it is shown in the Spanish Tourism Satellite Account. Given that, the aim of this paper is to analyse what factors can determine the incidence of temporary employment in Tourism activities in Spain and to discuss regional differences. As result, our first step is to identify the labour market characteristics of the different tourism activities. These results are clear influenced by the particularities of the different activities (labour market of transport activities is very different from hotels and restaurants activities) and not by a tourism characteristic. Thus, the second step is to analyse how tourism influence in the labour-market conditions after controlling for the particularities of the different tourism activities. In this case, we focus in just one characteristic of the labour market very associated with low-quality jobs; the share of workers with fixed-term jobs. Although Spain is one of the countries with the highest arrivals of tourists, those are not equally distributed by regions. This allows us to identify the degree of specialization of each region in tourism, and to analyse its impact in the share of workers with fixed-term contracts. Results show that the highest tourism specialization of the region decreases the share of workers with fixed-term contracts, after isolating the particularities of the different tourism activities. It seems that this low-quality characteristic disappear with the development of the sector in some regions.
Keywords: 330